Wavelet Codes and Their Implementation for Protection of NAND Flash Memory - Levina, A. B.; Taranov, S. V.; Kaplun, D. I.; Boyvalenkov, P. (Progress in Electromagnetics Research Symposium, 2019)
Nowadays wavelet theory finds implementations in many scientific aspects. It is implemented in the signal processing such as video and audio signals, in data transformation, and in many other areas. In this work, we present implementations of wavelets in coding theory and then apply resulting codes for the protection of NAND flash memory. Our application with new wavelet codes and their implementation in NAND flash memory prevents different types of errors and gives a higher level of security.